Audit Tenure Effects on Financial Reporting Quality and Independenc (gjstudies, 2017)
This research investigates the complex and non-linear relationship between audit tenureand the dual constructs of financial reporting quality and auditor independence, challengingthe prevailing assumption of a simple monotonic relationship. While existing literature predominantly focuses on either quality deterioration due to familiarity or improvement due tolearning, this study posits a triphasic model where the effects evolve distinctly across threetenure phases: the nascent phase (years 1-3), the maturation phase (years 4-7), and theelongated phase (years 8+). Our novel methodology employs a longitudinal, multi-methodapproach combining a proprietary dataset of granular audit process metrics—includingpartner-client meeting logs, workpaper review depth indices, and time allocation analytics—with experimental simulations of auditor judgment under varying tenure and pressurescenarios. We move beyond traditional outcome-based proxies for quality (e.g., discretionaryaccruals) to examine the integrity of the underlying audit process itself. The results reveal anuanced landscape: financial reporting quality, measured by process rigor and error detectionrates, improves significantly during the maturation phase due to accumulated client-specificknowledge and procedural efficiency, but plateaus and shows signs of procedural drift inthe elongated phase. Conversely, perceived and actual threats to independence exhibit adifferent trajectory, remaining low in the nascent phase, increasing subtly in the maturationphase as economic bonds and social familiarity deepen, and becoming most pronounced inthe elongated phase, often in subtle, non-confrontational forms of compromise. Crucially,the study identifies that the optimal tenure window for maximizing the quality-independenceequilibrium is narrower than mandated rotation policies suggest and is highly contingent onspecific governance moderators, such as audit committee diligence and the use of mandatory partner rotation within the firm. This research contributes a dynamic, phase-basedframework that disaggregates audit tenure effects, offering regulators and firms a more sophisticated evidence base for policy design beyond the blunt instrument of mandatory firmrotation.